Impact of the father’s migration in youth: when migration becomes abandonment - Obregón-Velasco, Nydia (Universidad Autónoma de Tamaulipas, 2015)
Seeking the wellbeing of the family is one of the main causes of migration from Mexico to the United States; parents go away in order to incre-ase the quality of life of the members of the family. However, the physical absence is often accompanied by emotional distance that can increase as time goes by. The objective of this research was to analyze the impact of the absence and abandonment that are experienced by the male and female young people from Cuitzeo, Michoacan, Mexico, due to the migration of the father. For this reason, we visited a public high school, where 13 students had experienced this situation. The data collection instruments were in-depth interviews, participant observation, talks, lectures, workshops and counseling conducted in the community. Findings indicate that young peopled described the departure of their father, at the beginning with hope, but as time went by they realized that their father gone away not only physically, but also emotionally from the family. Young people interpreted this experience as a type of abandonment. All the participants reported negative consequences related to the migration of their father. In a similar vein, they also considered the father’s absence and abandonment as a form of violence that is rooted in the gender identity constructions of this community, where men are educated to be the providers of the family and as parents with low levels of commitment in the parenting of their children.Archive XML (SciELO)